PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL, SPIRITUAL, DAN SOSIAL TERHADAP PERSEPSI MAHASISWA MENGENAI LABA AKUNTANSI - Yustisia, Satia; Prihatiningtias, Widya Yeney (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this study is to obtain empirical evidence about the influence of intellectual, emotional, spiritual, and social intelligence, simultaneously and partially on the students' perceptions about accounting profit. The research was conducted at 6 campuses in Malang, namely Universitas Brawijaya (UB), State University of Malang (UM), University of Muhammadiyah Malang (UMM), State Islamic University of Maulana Malik Ibrahim (UIN Maliki), Islamic University of Malang (Unisma), and Merdeka University (Unmer). The method used were descriptive and explanatory research, that was supported by the survey method. Data was collected through questionnaire method. The data were analyzed with descriptive statistics and linear regression. The results showed that: 1) intellectual, emotional, spiritual, and social intelligence has simultaneous significant effect on students’ perceptions about accounting profit, and 2) intellectual, emotional, spiritual, and social intelligence has partially significant effect on students' perceptions about accounting profit. This implied that with a higher intellectual, emotional, spiritual, and/or socially intelligence, the student will perceive the accounting profit as not only focusing on the orientation of the course material, but also has a other values than the monetary aspect. With this research result, the university expected to improve the quality of student intelligence, so that students are not only have about the materialistict concept of accounting profit, but also social and environmentalconcept as the aspect that can not be separated from the operational activities of the company.Keywords: intellectual intelligence (IQ), emotional intelligence (EQ), spiritualintelligence (SQ), social intelligence (SoSQ), student perceptions, accountingprofit.